Analysis of the Preliminary Study of Mathematical Communication Ability of Grade VII Students - Anjarwati, Eka; Mariani, Scolastika; Dewi, Nuriana Rachmani (Unnes Journal of Mathematics Education, 2025)
This study aims to determine students' mathematical communication ability in solving mathematical problems. This was descriptive research. The research subjects comprised 32 students in class VII-I SMP Negeri 39 Semarang. Data collection consists of a written test and an interview. Written tests were conducted to measure the achievement of indicators of mathematical communication ability, and interviews were conducted to obtain more in-depth data from students regarding mathematical communication ability. The results showed that in the first indicator, namely the ability to write to explain ideas or solutions in their own language, students achieved the very good category with a percentage of 93.75%. The second indicator, the ability to describe an idea or solution in the form of a diagram, table, or graph, is in the sufficient category with a percentage of 62.5%. The third indicator, the ability to express problems into mathematical models, obtained a low category with a rate of 43.75%. The fourth indicator, the ability to identify known information, what is asked, and the completion step, is in the category of sufficient, with a percentage of 56.25%. Meanwhile, the fifth indicator, namely the ability to draw conclusions, is in the poor category with a rate of 37.5%. These findings indicate that although the ability to write mathematical ideas is excellent, improvements are still needed in the indicators of mathematical model preparation and the conclusions drawn.